'The perception of fear conditioning urban space' - Fani Bakratsa (European Regional Science Association (ERSA), 2011)
The dominant metabolic system within urban environments often involves deep socio-economic inequalities, exploitative productive practices and a persistent sense of alienation among the vast majority of the population. The city itself spawns the conditions both for the development of actual criminality and, more perniciously, for the emergence of an acute perception of fear within the polis. Over the years, this perception has affected a whole array of societal elements including, quite significantly, the spatial structure of neighborhoods, urban forms and housing design. The big boom of gated communities signifies the development of social segregation and the tendency to ensure ontological security behind impenetrable walls. The development of off-center exclusive communities, parallel to the inner city impoverished neighborhoods establishes the "new ghettos trend". The new gated suburbs seem to have increased safety measures such as surveillance cameras, security personnel, high fences, moat-like structures, dead-end roads etc., involving a complex defensive architecture, in order to eliminate random and unaccounted movements, to enhance a sense of security and minimize the perception of fear. This paper examines the complex inter-determinations between perceived fear of urban otherness and spatial appropriation, urban forms and housing design, aspects whose functional attributes address almost exclusively the fear factor. It also presents the results of a comparative field study of the exclusive neighborhoods of Hampstead and Psychiko, in greater London and Athens respectively, where the material manifestations of the fear - urban character inter-relationship are examined, including road plans, pedestrian areas, home security systems, housing design elements and, perhaps most revealingly, real estate values.
Keywords: 330; exclusive suburbs; gated communities; perception of fear; defensive architecture; security